2019
DOI: 10.21608/ejh.2019.6757.1055
|View full text |Cite
|
Sign up to set email alerts
|

Histoloical and Biochemichal Study on the Toxic Effects of Bisphenol A on the Thyroid Gland of Adult Male Albino Rats and the Possible Protection by Selenium

Abstract: Background:The worldwide used bisphenol A (BPA) which is incorporated in many plastic industries is considered as an endocrine disruptor. Warnings raised by many agencies against the excessive use of such substances because of its confirmed hazardous effects. Selenium (Se) is known to have antioxidant role in living systems. Aim of the work:The aim of the current study was to evaluate the extent to which BPA can affect the thyroid gland structure and function and if there is any protective role for selenium. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
3
0
0
Order By: Relevance
“…This could be related to severe inflammation in the thyroid gland, which causes vasoconstriction and blood vessel congestion. Such findings coincide with that of other studies [42][43]. Furthermore, the current investigation revealed small sized empty follicles with damaged basement membranes and lumina fusion.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This could be related to severe inflammation in the thyroid gland, which causes vasoconstriction and blood vessel congestion. Such findings coincide with that of other studies [42][43]. Furthermore, the current investigation revealed small sized empty follicles with damaged basement membranes and lumina fusion.…”
Section: Discussionsupporting
confidence: 94%
“…Some follicular lumina of NaFtreated group showed desquamated follicular cells. In accordance, some researchers reported that sloughing of degenerated follicular epithelial cells is possible [43]. The histological alterations of the rat thyroid gland following NaF treatment can be due to the increased TSH level.…”
Section: Discussionsupporting
confidence: 67%
“…Evidence of hyperactivity was found in C cells such as follicular cells. These findings were also in agreement with Mohamed and Rateb [44] who reported that a hyperactive thyroid showed the presence of enlarged C cells distributed either in small groups or even singly. Some authors [45] attributed that to the high level of TSH, leading to hyperplasia and hypertrophy of C cells.…”
Section: Discussionsupporting
confidence: 92%